2018
DOI: 10.1080/14767058.2017.1419181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different combination of maternal and postnatal diet on adipose tissue morphology in male rat offspring

Abstract: Together with our previously published data, our results lead to the conclusion that alteration of postnatal diet can lead to TNF-α and adipocyte morphology changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Other work has shown that offspring of mothers consuming an obesogenic diet during gestation may be more prone to dietary-induced changes postnatally. For instance, rat offspring exposed to maternal obesity show greater morphological changes, including enhanced adipocyte hyperplasia in response to a postnatal high-fat diet [ 94 ]. Finally, some research suggests that programmed changes in offspring adipose biology may be permanent, as an exercise intervention in mothers fed a high-fat diet did not prevent the increased adiposity or trigger beneficial changes in insulin signaling component expression in their fetuses [ 95 ].…”
Section: Adipose Tissuesmentioning
confidence: 99%
“…Other work has shown that offspring of mothers consuming an obesogenic diet during gestation may be more prone to dietary-induced changes postnatally. For instance, rat offspring exposed to maternal obesity show greater morphological changes, including enhanced adipocyte hyperplasia in response to a postnatal high-fat diet [ 94 ]. Finally, some research suggests that programmed changes in offspring adipose biology may be permanent, as an exercise intervention in mothers fed a high-fat diet did not prevent the increased adiposity or trigger beneficial changes in insulin signaling component expression in their fetuses [ 95 ].…”
Section: Adipose Tissuesmentioning
confidence: 99%
“…It involved ten female Sprague Dawley rats randomly divided into two groups and fed either a diet rich in saturated fatty acids (HFD group) or control diet (CD group). The same diets were fed to their male offspring (n = 6 in each group) after birth and during the 3-week lactation period, as previously described [ 27 , 28 , 29 ]. The flowchart of the experimental procedure is shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Male rat offspring were euthanized at the age of 22 weeks. They were anaesthetized with a combination of ketamine and midazolam (Ketanest S, 25 mg/mL, 3 mL, Midazolam, 5 mg/mL, 1 mL, Pfizer, NY, USA) as described before [ 29 ]. Three compartments of WAT were isolated: subcutaneous, epididymal, and perirenal, and immediately stored in plastic tubes with formalin for fixation for a minimum of 12 h. After fixation, tissue samples were embedded in paraffin blocks, and then cut to 6 µm using a microtome (Leica, Vienna, Austria).…”
Section: Methodsmentioning
confidence: 99%
“…In animal models, in utero exposure to a diet rich in fats with or without prior maternal obesity, predisposes offspring to have increased body weight (46)(47)(48), increases the risk of developing obesity (46), increases tendencies to consume other substances of abuse such as nicotine and ethanol (47,49,50), and is associated with an increase in the incidence of psychiatric disorders ( Figure 2) (51-53). Ingestion of a HFD during pregnancy increases lipid accumulation in the placenta (54), while in offspring decreases the circulation of essential fatty acids (54), and increases the levels of triglycerides and adipocyte size (55,56). Prenatal HFD paired with a postnatal HFD regime can cause several effects in offspring that is exerted on a macro and microscale level, including a reduction in the variation of DNA methylation in peripheral organs and changes the expression of genes involved in inflammation and RNA processing (48).…”
Section: Dietary Fat On Stimulating Neurochemical Systems In the Hypomentioning
confidence: 99%